Transgender Portrayals in Tamil Movies: தமிழ்த் திரைப்படங்களில் சித்தரிக்கப்படும் திருநங்கைகள்: ஒரு பார்வை - Maraya , Ravindaran; Hemameera (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2021)
The aim of the paper is to offer an analysis of transgenders portrayals in selected Tamil movies. The Tamil Cinema, as an effective tool of entertainment tends to influence the viewers in many ways for its magnatic nature through moving images, music, dialogue, sound and special effects. The combined effets help one to easily exchange the sensation of actions and feelings casted by the role players. This in return, helping gradually the others in understanding the lives of others, like the transgenders. In particular, the movies and the storyline help us to understand their struggles and other societal norms revolving around them. There were not many studies have been carried out on Transgender issues though they were noted to be one of the class of citizens who were often facing neglection and humiliation, either from the members of the family, peers, and society. It could not be denied that their rights were not paid proper care by the government as well in many cases. Within the Indian society, they were identified as one of the most neglected and marginalized community, too. This descriptive study aimed at giving a general outlook of transgender outlook in the Tamil movies. There were a few attempts were seen in these movies to portray Transgender with different perspectives with view to change the worldview of society against the transgenders. These movies have shown them achievers in many spectrums, despite of long-lasting bullying, intolerance, and prejudice subjected towards them. On the other hand, there were a few movies that have portrayed the transgenders in an insensitive in an inaccurate way. This paper in general aimed at giving a general outlook of the transgenders portrayed in the movies, especially their nature and their living environment, livelihood and together with other related issues. இந்த ஆய்வு தமிழ்த் திரைப்படங்களில் திருநங்கைகளின் சித்தரிப்பைப் பற்றி ஆய்வு செய்கிறது. படங்கள், இசை, உரையாடல், ஒலி மற்றும் சிறப்பு விளைவுகளின் ஒருங்கிணைந்த தாக்கம் ஆழ்ந்த உணர்வுகளைப் பிரித்தெடுத்து, நம் வாழ்க்கையைப் பிரதிபலிக்க உதவும் என்பதால் தமிழ் சினிமா நம்மில் பலரைச் சக்திவாய்ந்த முறையில் பாதிக்கிறது. சினிமா என்பதால், சமூகத்தில் ஒரு சக்திவாய்ந்த ஊடகம் மக்களை ஒரே நேரத்தில் பாதிக்கிறது, அவை திருநங்கைகளின் வாழ்க்கையையும், நமது சமுதாயமும் கலாச்சாரமும் எவ்வாறு அவர்களைச் சுற்றி வருகின்றன என்பதை நன்கு புரிந்துகொள்ள உதவுகின்றன. திருநங்கைகள் குடும்பத்தினரிடமிருந்தும் அரசாங்கத்திலிருந்தும் புறக்கணிப்பை எதிர்கொள்கின்றனர். இந்திய சமுதாயத்தில் மிகவும் புறக்கணிக்கப்பட்ட மற்றும் ஓரங்கட்டப்பட்ட சமூகங்களில் ஒன்றாக அவர்கள் அடையாளம் காணப்பட்டனர். திருநங்கைகள் குறித்த பல்வேறு கருத்துகள் தமிழ் சினிமாவில் பல படங்களில் வெளிப்படுத்தப்பட்டுள்ளன. பெரும்பாலான படங்களில் ஒன்று அல்லது இரண்டு படங்கள் கூட திருநங்கைகளுக்குப் பெருமை சேர்க்கும் வகையில் வெளியிடப்படுகின்றன. தமிழ்த் திரைப்படங்களில் மட்டுமல்லாமல், திருநங்கைகள் பற்றிய பார்வையும் சமூகம் மாற்றியுள்ளது. கொடுமைப்படுத்துதல், சகிப்புத்தன்மை மற்றும் தப்பெண்ணம் ஆகியவற்றைத் தாங்கினாலும் திருநங்கைகள் பல நிலைகளில் சாதிக்கின்றனர். சில திரைப்படங்கள் திருநங்கைகளை அவர்களின் வாழ்க்கையின் உணர்ச்சியற்ற மற்றும் தவறான முறையில் சித்தரித்தன. இரண்டாம்நிலை தரவு மற்றும் இலக்கிய மதிப்புரைகளின் அடிப்படையில், இந்த ஆய்வு தமிழ்த் திரைப்படங்களில் திருநங்கைகளின் சித்தரிப்பு மீது கவனம் செலுத்துகிறது. இது அவர்களின் வாழ்க்கைச் சூழல், வாழ்வாதாரம் மற்றும் பல சிக்கல்களை வெளிப்படுத்துகிறது.